An Overview of the Pressurized Thermal Shock Issue in the Context of the NURESIM Project. (14th October 2009) - Lucas, D.; Bestion, D.; Bodèle, E.; Coste, P.; Scheuerer, M.; D'Auria, F.; Mazzini, D.; Smith, B.; Tiselj, I.; Martin, A.; Lakehal, D.; Seynhaeve, J.-M.; et al.
Abstract : Within the European Integrated Project NURESIM, the simulation of PTS is investigated. Some accident scenarios for Pressurized Water Reactors may cause Emergency Core Coolant injection into the cold leg leading to PTS situations. They imply the formation of temperature gradients in the thick vessel walls with consequent localized stresses and the potential for propagation of possible flaws present in the material. This paper focuses on two-phase conditions that are potentially at the origin of PTS. It summarizes recent advances in the understanding of the two-phase phenomena occurring within the geometric region of the nuclear reactor, that is, the cold leg and the downcomer, where the "PTS fluid-dynamics" is relevant. Available experimental data for validation of two-phase CFD simulation tools are reviewed and the capabilities of such tools to capture each basic phenomenon are discussed. Key conclusions show that several two-phase flow subphenomena are involved and can individually be simulated at least at a qualitative level, but the capability to simulate their interaction and the overall system performance is still limited. In the near term, one may envisage a simplified treatment of two-phase PTS transients by neglecting some effects which are not yet well controlled, leading to slightly conservative predictions.